Effect of Varying Postmortem Deboning Time and Sampling Position on Visible and near Infrared Spectra of Broiler Breast Filets - Hawkins , S.A.; Zhuang, H.; Sohn, M.; Windham, W.R. (International Journal of Poultry Science, 2014)
Visible-Near Infrared spectroscopy (Vis-NIR) was used to characterize broiler breast filets with varied deboning times and identify how the side and position of the sampling affects the chemometric analysis and prediction capabilities. This study served to identify what differences, if any, exist when collecting spectra from the skin side and the medial side of the breast filets. In addition to the side of the filet, two different positions, anterior and posterior, on the filet were also probed spectroscopically. The comparison of the region and side of sampling of the breast filets has been previously unreported. The breast filets under investigation were subjected to different post-mortem deboning times. The right and left breast filets from each carcass were both used, but were deboned at different times. The results of this study show that the side of the filet has more impact on the spectra than does the position of the sampled area. The data analysis also shows that the spectra from the skin side are more useful for separation of samples by deboning time.